2008
DOI: 10.1074/jbc.m803026200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Catalytic Domain of the Mitotic Checkpoint Kinase Mps1 in Complex with SP600125

Abstract: Chromosomal instability can result from defective control of checkpoints and is associated with malignant cell growth. Monopolar spindle 1 (Mps1) is a dual-specificity protein kinase that has important roles in the prevention of aneuploidy during the cell cycle and might therefore be a potential target for new therapeutic agents in the treatment of cancer. To gain insights into the molecular mechanism of Mps1 inhibition by small molecules, we determined the x-ray structure of Mps1, both alone and in complex wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
76
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 27 publications
6
76
1
Order By: Relevance
“…Peptide sequence m/z the Mps1 protein kinase [21]. Our analyses failed to detect any nonphosphorylated T676, while the stoichiometry of phosphorylation of T686 was 95% Ϯ 1%, indicating that both sites are highly modified.…”
Section: Workflowcontrasting
confidence: 48%
See 2 more Smart Citations
“…Peptide sequence m/z the Mps1 protein kinase [21]. Our analyses failed to detect any nonphosphorylated T676, while the stoichiometry of phosphorylation of T686 was 95% Ϯ 1%, indicating that both sites are highly modified.…”
Section: Workflowcontrasting
confidence: 48%
“…Mps1 is a mitotic protein kinase required for the spindle assembly checkpoint (SAC) in many organisms including yeast, flies, zebrafish, frogs, and humans [4,21]. Autophosphorylation of Mps1 is required for full activity in vitro with complex changes in the extent and location of phosphorylation known to be responsible for regulating protein kinase function [4,21].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The carboxyl terminus of Mps1 is disordered in both of the reported Mps1 crystal structures (23,29). The carboxyl terminus of Mps1 does not appear to be required for its autophosphorylation but is critical for transphosphorylation of the substrates (Fig.…”
Section: Table 2 Enzyme Kinetic Constants From the Two Substrate Kinementioning
confidence: 99%
“…Crystallographic analysis of Mps1 indicated that whereas the kinase domain in the carboxyl-terminal region of Mps1 adopts a canonical kinase fold, the 65-residue carboxyl-terminal tail of Mps1 is unstructured (23,29) (Fig. 2A).…”
Section: Cellular Abundance Of Mps1 Cdk1mentioning
confidence: 99%